Seismic microzonation map of Puducherry region, india - Revathi, P. (Journal of Structural Engineering, 2024)
A first level seismic hazard microzonation map for Puducherry, an union territory in southern India, is presented in this paper. A probablistic seismic hazard analysis is carried out using the earthquake catalogue and seismo-tectonic data available over a radius of 300 km around Puducherry city. Guttenberg-Richter’s recurrence relationship and attenuation relationship for peninsular India are adopted to estimate peak ground acceleration at bed rock level (PGA). Geotechnical data are collected for various locations in the study region and the shear wave velocity is estimated empirically. The results of the investigation are presented in the form of PGA corresponding to a 10 % probability of exceedance in 50 years. The maximum PGA for Puducherry is obtained as 0.133g. On comparing, the estimated PGA values with that of IS 1893-2002 recommendations, it is concluded that the code based values are not conservative for Puducherry region.